ANALYSIS OF THE IMPLEMENTATION OF THE WEIGH-IN OF EXECUTIVE NURSES IN THE PATIENT ROOM OF UNDATA HOSPITAL - Sugyarso; Natsir, Syahir; Adda, Harnida Wahyuni (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
The purpose of this study was to understand the process of weighing and receiving by executive nurses in 10 inpatient rooms of Undata Hospital, Palu, Central Sulawesi Province. The research subjects included 65 executive nurses working in the hospital. Purposive sampling was the sampling method used in this study, where the researcher selected respondents from the population based on criteria determined by the researcher. The conclusion of the results of this study states that a series of nurse handover processes in the inpatient room of Undata Hospital, Palu, Central Sulawesi Province have been implemented, but 45 respondents (69%) stated that the handover mechanism was in accordance with the SOP and 20 respondents (31%) stated that the implementation was not in accordance with the SOP.In the handover method, there were 39 respondents (60%) who stated that it was in accordance with the SOP and 26 respondents (40%) who stated that it was not in accordance with the SOP. Regarding the content / information of the weigh-in, 47 respondents (72%) stated that it was in accordance with the SOP and as many as 18 respondents (18%) stated that it was not in accordance with the SOP. As well as obstacles such as things that are forgotten to be conveyed, noise, patient calls and critical situations of patients during weigh-in, 50 respondents (77%) stated that they could handle it well and as many as 15 respondents (23%) stated that there were obstacles in the process of weigh-in in the Undata Hospital inpatient room that could not be handled at all, but could be minimized.